Предмет: Алгебра,
автор: missisconstant1
cos2t+1-sin2t
Ответы
Автор ответа:
0
cos(2t)=cos^2(t)-sin^2(t)
sin(2t)=2*sin(t)*cos(t)
1=sin^(t)+cos^2(t)
cos^2(t)-sin^2(t)+sin^(t)+cos^2(t)-2*sin(t)*cos(t)=0
2cos(t)*(cos(t)-sin(t))=0
Решение:или cos(t)=0 или cos(t)=sin(t)
t=pi/2+pi*n tg(t)=1
t=pi/4 + pi*k
sin(2t)=2*sin(t)*cos(t)
1=sin^(t)+cos^2(t)
cos^2(t)-sin^2(t)+sin^(t)+cos^2(t)-2*sin(t)*cos(t)=0
2cos(t)*(cos(t)-sin(t))=0
Решение:или cos(t)=0 или cos(t)=sin(t)
t=pi/2+pi*n tg(t)=1
t=pi/4 + pi*k
Похожие вопросы
Предмет: Литература,
автор: Sisi4ki228666
Предмет: История,
автор: prakudinavika
Предмет: Геометрия,
автор: garaevavaleria94
Предмет: Математика,
автор: MrMayk